Voltage and Calcium Imaging of Brain Activity - Rad, Masoud Sepehri; Choi, Yunsook; Cohen, Lawrence B.; Baker, Bradley J.; Zhong, Sheng; Storace, Douglas A.; Braubach, Oliver R. (CELL PRESS, 2017)
Sensors for imaging brain activity have been under development for almost 50 years. The development of some of these tools is relatively mature, whereas qualitative improvements of others are needed and are actively pursued. In particular, genetically encoded voltage indicators are just now starting to be used to answer neurobiological questions and, at the same time, more than 10 laboratories are working to improve them. In this Biophysical Perspective, we attempt to discuss the present state of the art and indicate areas of active development.
Keywords: ALL-OPTICAL ELECTROPHYSIOLOGY; NEOCORTICAL PYRAMIDAL NEURONS; SENSITIVE FLUORESCENT PROTEIN; OLFACTORY SENSORY NEURONS; ACTION-POTENTIALS; SENSING DOMAIN; ELECTRICAL-ACTIVITY; DENDRITIC SPINES; MEMBRANE VOLTAGE; PROBE